Керамічний комплекс ранньоскіфського часу із урочища Китай Гора у Пороссі - Романюк, В.В. (Археологія і давня історія України, 2020)
В публікації розглянуто комплекс ліплених посудин (орнаментована корчага і два горщички), виявлені в урочищі Китай Гора поблизу с. Крива Таращанського р-ну Київської обл. Посудини знаходилися під невеликим насипом на глибині близько 2 м в перегорнутому стані. За аналогіями комплекс можна датувати другою половиною VII ст. до н. е. The publication is devoted to the characteristics of the ceramic complex discovered in 2019 in the burial mound 1, located near the village of Kryva (China- Gora tract), Tarashchansky district, Kyiv region. Under a small mound in the grave pit at a depth of about 2 m were three sculpted vessels (the large pot and two smaller) in an inverted position. The large pot is decorated with carved geometric ornaments, painted with white paste. Both pots are tulip-shaped. The most expressive analogies (from the collection of F. F. Kunderevich and the mound 1 1999) look undoubtedly more archaic. According to these analogies, the ceramic complex from the Chinatown tract can be dated to the second half of the 7th century BC. Korchaga from the Chinatown complex is probably later. That is the period of «late geometry», when the decorative traditions of the Jabotins gradually disappear. The middle of the 7th century. BC. is a conditional boundary from which the violation of the tradition of Jabotin geometry in the Black Sea region begins.